2023
DOI: 10.3389/fncel.2023.1129097
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical considerations and supporting evidence for the primary role of source geometry on field potential amplitude and spatial extent

Abstract: Field potential (FP) recording is an accessible means to capture the shifts in the activity of neuron populations. However, the spatial and composite nature of these signals has largely been ignored, at least until it became technically possible to separate activities from co-activated sources in different structures or those that overlap in a volume. The pathway-specificity of mesoscopic sources has provided an anatomical reference that facilitates transcending from theoretical analysis to the exploration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 106 publications
(213 reference statements)
0
5
0
Order By: Relevance
“…Actually, they belong to the few connections that contribute significantly to FPs. In former studies we showed that most pathways do not contribute to FPs, either due to the inadequate spatial geometry of microscopic currents ( Herreras et al, 2023 ) or because the low level of activity does not accumulate enough variance to be discriminated by the ICA ( Herreras et al, 2015 ). However, in these loose pieces of the map, we have several that are key and allow us to glimpse the overall flow of activity and some of its bilateral characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Actually, they belong to the few connections that contribute significantly to FPs. In former studies we showed that most pathways do not contribute to FPs, either due to the inadequate spatial geometry of microscopic currents ( Herreras et al, 2023 ) or because the low level of activity does not accumulate enough variance to be discriminated by the ICA ( Herreras et al, 2015 ). However, in these loose pieces of the map, we have several that are key and allow us to glimpse the overall flow of activity and some of its bilateral characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Methods to increase the temporal precision of separation have been advanced, but they may not achieve sufficient precision in some epochs ( Benito et al, 2014 , 2016 ). Without optimization measures, accurate extraction of gamma waves in strongly overlapping DG generators (e.g., Fernández-Ruiz et al, 2021 ) is highly susceptible to error, while being more reliable when applied to CA1 gamma sources (see Herreras et al, 2023 for a repertoire of gamma-related phenomena). In this study, we have opted for cautious use of correlation or spectral coherence tests, which are suitable for studying global flow and coherence between paired generators of bilateral circuits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations